PERTUMBUHAN EKONOMI INDONESIA: Determinan dan Prospeknya - Ma’ruf, Ahmad; Wihastuti, Latri (Jurnal Ekonomi & Studi Pembangunan, 2008)
This study analyzes the influence of government expenditure and some other variables that affect the long-term economic growth at provincial level in Indonesia. This study uses panel data analysis which consists of 26 provinces during the period 1980-2006. Data used has been through stasioneritas tests using Augmented Dickey Fuller test (ADF) - Fisher for panel data suggested by Madalla and Wu (1999). The result, stationary data on the first level of difference. This study shows that the coefficient of real government spending is significantly positive. This means that government expenditure has an important role in improving economic growth in Indonesia. pengeluaran pemerintah secara agregat.